The legal treatment of ESG objectives and the modification of the duty of diligence in the proposed Directive on due diligence - Moya Ballester, Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The objective of this work is to analyze the impact that new legislative developments in the field of ESG criteria have on corporate regulations. Specifically, the work analyzes the possible change in the conception of social interest as a result of the legislative developments on sustainability, and in particular, the possible changes that this matter may have produced in the fiduciary duties. To do this, it is necessary not only to analyze the proposed directive on due diligence, but also the concept of corporate interest itself and its relationship with the duty of diligence and the duty of loyalty.